Redesain Cold Heading Dies Melalui Pendekatan Metode FMEA dan DFM di PT. ZYX - Deni Setiawan; Annisa Indah Pratiwi; Amelia Nur Feriza (OPSI, 2022)
PT. ZYX is a foreign company automotive component sector for four-wheeled vehicles. In their third year of mass production, the production capacity reached 116 million pcs, resulting in the high cost of Dies purchase for Cold Heading machines. This condition worsened because things such as Dies having a low lifetime and the lead time for Dies purchasement is in the range of 20-40 days or more, which has the potential to cause machine downtime. This study aims to redesign the Dies of Cold Heading machine used today. Completion of the design uses the Pareto diagram analysis, FMEA, and DFM. The analysis result using the FMEA method shows the highest RPN value of 336 with the potential for insert carbide failure that cracks during assembly. The recommended corrective action is to make assembly support components, namely pokayoke parts, and make work instructions for replacing carbide inserts on Dies. The analysis results using the DFM method shows a change in term of cost. The cost for 1 unit of Dies purchasement was initially Rp. 10,247,113.00, but it dwindles to Rp. 4,623,914.23. Using the redesign to make case dies, lock nuts, collets, and stoppers components, resulted in cost efficiency of 54.87%.